KONTRIBUSI TENAGA KERJA DALAM KELUARGA TERHADAP PENDAPATAN USAHATANI BAWANG DAUN (Allium fistulosum L.) DI KELURAHAN LANDASAN ULIN UTARA KOTA BANJARBARU - Subhan Fitriadi; Eddy Triatmoko; Rizky Putri AS (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2017)
The purpose of this research is to know the revenue,the explicit cost,income andcontribution of workers in family to total income farming onion . This research was conducted in januari to maret 2017 at Kelurahan Landasan Ulin Utara Banjarbaru. The puposive sampling metode used was by observing 30 farmers in syamsudin Noor who planted land 1-3 ha. The Average result of the revenue is Rp. 17.250.000 / farmer, the average explicit cost is Rp. 5.761.131/farmer, and the average income is 11.488.869, / farmer, and contribution workers in family 18 % greather than workers out family 1,31 % .Because majority of workers used are from the familyto the farmers it self, this affects a lot on the income of onion farming revenue.